Sexual dimorphism of colorectal cancer in humans and colorectal tumors in a murine model - Rodríguez-Santiago, Yair; Terrazas-Valdés, Luis Ignacio; Nava-Castro, Karen Elizabeth; Del Río-Araiza, Víctor Hugo; Garay-Canales, Claudia Angélica; Morales-Montor, Jorge (Frontiers in Oncology, 2024)
In colorectal cancer, men exhibit a higher incidence than women, and there is a disturbance in the levels of sex steroids in serum in patients with this disease. Consistently, in animals, males have greater tumor growth than females in diverse models. Nevertheless, the role of sex steroids is not well established. For that, we analyzed the effect of the principal gonadal sex steroids in both sexes. We determined sex as a statistically risk factor for colorectal cancer with data obtained from GLOBOCAN database. To induce colorectal tumors, we used the gold standard chemical method of azoxymethane and dextran sulphate of sodium. To evaluate the role of sex steroids, we gonadectomized independent males and female animals, reconstituting and substituting them with 17 estradiol and dihydrotestosterone. Finally, we determined, in vitro, the proliferation of a human cell line exposed to 17 estradiol, testosterone, or dihydrotestosterone. Sex, as a risk factor for colorectal cancer, showed a statistically significant susceptibility of men over 50 years old. Our results showed that in vivo, males develop a greater number of tumors and with a larger size than females. In males, orchiectomy prevents tumor growth, whereas in females, ovariectomy promotes the development of neoplasms. DHT acts as a protumoral agent in both sexes. 17 estradiol reduces tumor growth in females but enhances it in males, showing a dimorphic effect. In vitro studies reveal that estradiol decreases the proliferation of the HCT-116 colon cancer cell line, while testosterone boosts proliferation in these cells. Interestingly, dihydrotestosterone does not influence proliferation.